2016
DOI: 10.1002/chin.201644045
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A General Catalyst for Site‐Selective C(sp3)—H Bond Amination of Activated Secondary over Tertiary Alkyl C(sp3)—H Bonds.

Abstract: A newly designed silver complex generated in situ is applied to nitrene insertion into propargylic, allylic, and benzylic C—H bonds competing to tertiary alkyl C(sp3)—H bonds are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…To further elucidate the relative roles of steric and electronic effects in benzosultam formation, substrates 8-11 containing alkyl branching were investigated (Table 3). Although previous work with [Ag(Py 5 Me 2 )OTf] 2 33 indicated that sterics would play a predominant role in discriminating between the α and β C-H bonds, results with 8 and 9 proved surprising. Amidation of the tertiary C-H bonds were heavily favoured, leading to single products, irrespective of the location of the methinyl C-H.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…To further elucidate the relative roles of steric and electronic effects in benzosultam formation, substrates 8-11 containing alkyl branching were investigated (Table 3). Although previous work with [Ag(Py 5 Me 2 )OTf] 2 33 indicated that sterics would play a predominant role in discriminating between the α and β C-H bonds, results with 8 and 9 proved surprising. Amidation of the tertiary C-H bonds were heavily favoured, leading to single products, irrespective of the location of the methinyl C-H.…”
Section: Resultsmentioning
confidence: 87%
“…[31][32][33][34] In our hands, Ag(I) catalysis displays significant synthetic versatility, enabling tunable, chemoselective aziridination versus allylic C-H insertion in alkenes and allenes, 31,34 effective direct amination of propargylic C-H bonds in the presence of competing insertion sites, 32 and tunable, site-selective C-H amidation of competing C-H bonds. 33 The selective functionalization of C-H bonds using group transfer reactions remains of intense interest, owing to the ubiquity of these bonds in complex organic frameworks. Regioselectivity amongst vicinal methylene C-H bonds is a particularly daunting challenge, as interrelated steric and electronic environments often preclude effective site-selective functionalization.…”
Section: Introductionmentioning
confidence: 99%